Phonology, The Sounds in a Speech in Terms - qizi, Uzoqova Marjona Sherali (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
This article explores the field of phonology, focusing on the analysis of speech sounds within various linguistic frameworks. Phonology, as a branch of linguistics, examines the systematic organization of sounds in languages, emphasizing the rules and patterns that govern their use. The study provides an overview of key phonological concepts, such as phonemes, allophones, and distinctive features, and discusses how these elements interact to create meaningful speech. By examining contemporary approaches to phonological analysis, including both theoretical and experimental methods, the article sheds light on how phonologists understand and categorize the sounds in human speech.